Penampilan Morfologi dan Sitologi Tanaman Semangka (Citrullus lanatus Thunb.) Hasil Induksi Senyawa Kolkisin - Aswat, Amarilla; Hayati, PK Dewi; Sutoyo; Warnita; Kuswandi (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
Seedless watermelons, both seeds and fruits, possess a significantly higher economic value than their seeded counterparts. Serif Saga Agrihorti, a variety developed by the Tropical Fruit Research Institute, offers several advantages, including a sweet taste, high fruit yield, bright red flesh, and large fruit size. However, it is characterized by a relatively high number of seeds. The development of a new seedless variety from Serif Saga Agrihorti is crucial. Polyploid induction using mutagenic agents like colchicine is an effective method to obtain tetraploid female parents. This study aimed to identify the optimal method and colchicine concentration for inducing polyploidy in watermelons and to produce putative tetraploid plants. Polyploid induction was conducted using two methods: directly applying colchicine solution to plant shoots and soaking seeds in colchicine solution for 24 and 48 hours at concentrations of 0.2% and 0.4%. The observed traits included stem diameter, leaf length and width, stomatal length and width, pollen diameter, pollen viability, male and female flowering periods, harvesting time, fruit weight, fruit diameter, seed count, and seed dimensions (length and width). Data were analyzed using an unpaired t-test using the Statistical Tools for Agricultural Research (STAR) software. The results identified four putative tetraploid genotypes based on morphological observations of pollen diameter, stomatal size, and seed dimensions. In conclusion, seed soaking in colchicine solution effectively induces polyploidy in watermelons compared to shoot application.